Estimating evapotranspiration and crop coefficient of vegetable crops using pot micro-lysimeters - Octura, Josh Elisha R.; Gadiaware, Paisar L.; Octura, Elpidio R. (2020)
Irrigation for crop production constitutes the most part of agricultural water worldwide. As most of the water withdrawn by agriculture is lost through crop evapotranspiration (ETC), efficient water management requires accurate and reliable estimation of ETC. To date, available methods for estimating ETC require expensive devices and extensive meteorological information, which become a problem in areas with no instruments and with limited data. The present study aimed to evaluate the performance of a technique to estimate ETC and crop coefficient (KC) of selected vegetable crops (lettuce, mustard, onion, bush bean, and ?pechay?) using small plastic pots as micro-lysimeters under screen house conditions. Daily rainfall, reference crop evapotranspiration (ETO), and ETC were recorded. Correlation analysis between ETO and ETC showed a significant positive correlation in lettuce (R = 0.736), pechay (R = 0.687), onion (R = 0.761), and mustard (R = 0.467). The KC values of vegetable crops were obtained and the KC curve for each crop was generated by plotting the KC with respect to the stages of growth. Comparison between KC curves of crops obtained using the present technique with the generalized KC curve by the FAO56 Penman-Monteith (FAO56PM), the standard method for estimating ETC and KC, revealed a significant positive correlation in mustard (R = 0.998), onion (R = 0.982), and bush bean (R = 0.800) ? suggesting that the KC curves of most crops obtained by using the present technique is comparable with the standard generalized KC curve by the FAO56PM. Taken together, these findings suggest that the present technique provided a close approximation of the water requirements of the crops tested. Since the technique is relatively simple and requires minimum input parameters for estimating ETC and KC compared to the standard method, the technique may be used as an alternative in remote areas where meteorological information is limited, as well as in places where urban agriculture is commonly practiced.